Implementing the Cue Method to Support Qur'an Memorization among Deaf Students: A Study at the BAZNAS BAZIS Disability Tahfiz Boarding School Jakarta - Hasanah, Holiyatul; Slamet, Ubaidillah Al-Ghifary (el-Tarbawi, 2025)
This study aims to examine the implementation of the cue method in supporting Qur'an memorization among deaf students and to identify the factors that facilitate and hinder its application. The research was conducted at the BAZNAS BAZIS Disability Tahfiz Boarding School in Jakarta, an Islamic educational institution dedicated to students with special needs. This study employed a qualitative field research design. Primary data were collected through classroom observations, in-depth interviews with teachers and students, and documentation analysis. The collected data were analyzed using a descriptive-analytical approach involving three stages: data reduction, data display, and conclusion drawing. The findings reveal that the implementation of the cue method in Qur'an memorization for deaf students is carried out through four main stages: instructional preparation and planning, provision of learning facilities and supporting media, implementation of the cue-based memorization method, and continuous monitoring and evaluation of students’ progress. The effectiveness of this method is supported by several factors, including strong institutional commitment to inclusive education, structured learning schedules, adaptive teaching strategies, and adequate psychological and physiological support for students. However, several challenges were identified, particularly variations in students’ cognitive abilities and learning attitudes, as well as limited parental and community involvement in supporting the memorization process. These findings highlight the importance of adaptive pedagogical approaches in Qur'anic education for students with hearing impairments and demonstrate the potential of cue-based methods in supporting inclusive religious learning environments.